Silica nanoparticle supported lipid bilayers for gene delivery - Liu, Juewen (2009)
Silica nanoparticle supported cationic lipids can effectively bind plasmid DNAs and transfect mammalian cells with an efficiency that depends on both the particle size and lipid composition; here the gene delivery and expression process has been confirmed by confocal fluorescence microscopy.